The occurrence of microplastics in fresh surface waters - Mrowiec, Bożena (Instal, 2022)
The paper presents characteristics of plastic pollutants – microplastics (MPs), their occurrence in fresh surface waters on different continents and methods of removing these pollutants from water. The investigations show the concentration of MPs varies considerably in fresh waters, from 10-2 to 108 particles/m3. From the point of view of using surface waters as drinking water, the presence of MPs becomes a challenge for designers and technologists of water treatment systems. Effective methods of MPs removing from water include membrane processes and rapid filtration. Chemical methods such as coagulation, electrocoagulation and advanced oxidation are being refined towards the effective MPs elimination. The contamination of inland waters by MPs indicates that immediate actions are required to limit the discharge of MPs into the aquatic environment and effective water treatment.